Treatment and management of chronic thromboembolic pulmonary hypertension (CTEPH): A global cross‐sectional scientific survey (CLARITY) - Nika Skoro‐Sajer; Karen Sheares; Paul Forfia; Gustavo A. Heresi; Mitja Jevnikar; Grzegorz Kopeć; Olga Moiseeva; Mario Terra‐Filho; Helen Whitford; Zhenguo Zhai; Amélie Beaudet; Virginie Gressin; et al. (Pulmonary Circulation, 2024)
Abstract Advances in the treatment of chronic thromboembolic pulmonary hypertension (CTEPH) over the past decade changed the disease landscape, yet global insight on clinical practices remains limited. The CTEPH global cross‐sectional scientific survey (CLARITY) aimed to gather information on the current diagnosis, treatment, and management of CTEPH and to identify unmet medical needs. This paper focuses on the treatment and management of CTEPH patients. The survey was circulated to hospital‐based medical specialists through Scientific Societies and other medical organizations from September 2021 to May 2022. The majority of the 212 respondents involved in the treatment of CTEPH were from centers performing up to 50 pulmonary endarterectomy (PEA) and/or balloon pulmonary angioplasty (BPA) procedures per year. Variation was observed in the reported proportion of patients deemed eligible for PEA/BPA, as well as those that underwent the procedures, including multimodal treatment and subsequent follow‐up practices. Prescription of pulmonary arterial hypertension‐specific therapy was reported for a variable proportion of patients in the preoperative setting and in most nonoperable patients. Reported use of vitamin K antagonists and direct oral anticoagulants was similar (86% vs. 82%) but driven by different factors. This study presents heterogeneity in treatment approaches for CTEPH, which may be attributed to center‐specific experience and region‐specific barriers to care, highlighting the need for new clinical and cohort studies, comprehensive clinical guidelines, and continued education.